Use and traditional knowledge of Byrsonima crassifolia and B. coccolobifolia (Malpighiaceae) in a Makuxi community of the Roraima savanna, northern Brazil - Rodrigo Leonardo Costa de OLIVEIRA; Veridiana Vizoni SCUDELLER; Reinaldo Imbrozio BARBOSA (Acta Amazonica, 2017)
ABSTRACT Byrsonima crassifolia and B. coccolobifolia, popularly known as mirixis, muricis, mantecos or nances, are common fruit species in the Amazonian savannas. Their fruits are used in the preparation of juices and other beverages, while the other parts of the plants are used for different purposes in some indigenous communities. The aim of the present ethnobotanical study was to investigate the knowledge and traditional uses of mirixis in the Darora Indigenous Community, of the Makuxi ethnicity, in the São Marcos Indigenous Land, state of Roraima, northern Brazil. The knowledge on these species among the residents was analyzed considering their gender and age. A survey was carried out by means of semi-structured interviews with 60 respondents (36 men and 24 women), between 18 and 84 years of age. Data from the interviewees was compared between genders and two age groups (< 40 and ≥ 40 years of age). Ethnobotanical indices (Informant diversity value; Informant equability value) were calculated, and no significant differences were found in the diversity of uses between genders (U = 283.0000, p > 0.05) and age groups (U = 359.5000, p > 0.05), indicating that the knowledge on the species is evenly distributed among residents. Results show that both species are used for different purposes in the food, fuelwood and medicinal categories in the Darora Community, and this knowledge is widely shared among adult men and women of all ages.